Hubungan Literasi Kesehatan Dengan Perilaku Vaksinasi Covid-19 Pada Masyarakat Di Desa Panusupan Kecamatan Rembang Kabupaten Purbalingga - Anggara, Yayan Bayu; Kumala Dewi, Feti; Wahyu Ningrum, Ema (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Vaccines are the most effective way to prevent infectious diseases. Vaccine hesitancy and misinformation present major barriers to achieving community coverage and immunity. Evidence-based health literacy needs to be developed as an effective strategy to encourage vaccine uptake. The aim of the study was to determine the relationship between health literacy and covid-19 vaccination behaviour in the community in Panusupan Village, Rembang Subdistrict, Purbalingga Regency. The research design was a correlation study survey with a cross sectional approach. Sample of this study were residents targeted for covid-19 vaccination in Panusupan Village, Rembang Subdistrict, Purbalingga Regency, 92 respondents using proportionate stratified random sampling technique. Research instrument used the eHealth Literacy Scale During Covid Indonesia Version questionnaire. Data analysis using the spearman-rank. Results showed spearman rank test obtained a p-value of 0.0001 ≤ α (0.05) and rho value: 0.499. The conclusion is that there is a weak relationship with a positive direction between health literacy and covid-19 vaccination behaviour in the community in Panusupan Village, Rembang District, Purbalingga Regency.